Mesh rotating reactors for biofilm pre-treatment of wastewaters – Influence of media type on microbial activity, viability and performance - Hassard, Francis; Biddle, Jeremy R.; Cartmell, Elise; Stephenson, Tom (Elsevier, 2016)
The impact of using different plastic mesh in rotating biofilm reactors (RBRs) on the treatment performance, biofilm activity and viability under varying organic loading rates (OLRs) was investigated. Laboratory-scale RBRs treating real wastewater were operated under OLR loading conditions typical of pre-treatment processes. A fully-crossed, three-factorial design series of experiments was undertaken with low and high surface area mesh made from polyvinyl chloride (PVC) and polypropylene (PP) operated at low, medium, high and very high OLR. The maximum volumetric removal rate of 2.4 kg sCOD m3 d−1 occurred at the high OLR, for low surface area mesh, irrespective of plastic used. The highest OLR at which nitrification could be attained was 35 g sCOD m−2 d−1. The biofilm growth decreased under medium compared to low OLR on all mesh. This coincided with a ∼2 fold decrease in the microbial viability. Higher surface area mesh was important for high nitrification rates at medium OLR (p < 0.05). In contrast the low surface area PVC and PP mesh was best at very high OLR (160 g sCOD m−2 d−1 or ∼320 g BOD5 m−2 d−1) for bulk organics removal (p < 0.05). Therefore, lower surface area mesh is recommended for wastewater pre-treatments at high OLR, whilst high surface area mesh was best for elevated nitrification rates at medium OLR. The microbial activity and viability had a strong positive correlation with OLR (R2 = 0.92, p < 0.001 and 0.81, p < 0.001 respectively). The microbial activity and viability also positively correlated (R2 = 0.4, p < 0.05 and 0.29, p < 0.01 respectively) to the sCOD removal performance but not the ammonia removal in mesh RBRs. This confirms the importance of maintaining biofilm activity and viability for bulk organics removal in biofilm processes in wastewater treatment.
Keywords: Biofilm; Microbial activity; Nitrogen; Organic loading; Viability; Wastewater